Services and psychosocial care after disasters – qualitative findings from South East Europe - Ajduković, Dean (Array, 2009)
Mapping of services for psychosocial care of trauma victims after disasters within The European Network for Traumatic Stress (TENTS) included qualitative data. Interviews and focus groups were done with key informants in Croatia, Bosnia & Herzegovina, Serbia, Slovenia and Macedonia. They included mental health providers and managers from governmental and non-governmental services involved in serving traumatized populations (psychiatric hospitals, community mental health centres, rescue services, disaster planning authorities, voluntary organizations, Red Cross, professional associations). The number of informants from 9 (Croatia, Serbia) to 3 (Slovenia, Macedonia) reflect the current level of delivery of psychosocial care and the stage of planning services after disasters. In Croatia, Slovenia and Serbia, the master planning is in the early stage, while it is still not on the agenda in Bosnia & Herzegovina and Macedonia. More experiences with traumatized survivors, mostly resulting from the recent war, is related to more advanced services and planning of psychosocial care for victims of disasters. Croatia has a network of 136 providers specifically trained in community-based psychosocial crisis interventions capable to respond on a short notice. It was developed within a non-governmental organization over 13 years and will become a part of the national disaster response.